Media Introduction to Aircraft Engine Collections Using QR Code at Nurtanio Laboratory ITD Adisutjipto - Yuliani Indrianingsih; Berland Vardy Pratama; Salam Aryanto; Dwi Nugraheny (Information Technology and Science (ITScience), 2023)
The Public Relations and New Student Admissions Center of the Adisutjipto Dirgantara Technology Institute often collaborates with high schools and vocational schools both from Java and outside Java in terms of campus visits and has a program called Campus Tour. In carrying out campus tour activities, there are several problems that often arise. Therefore, an application called Education for Aero Engineering Adisutjipto (TORERO) was created with a 360° virtual reality tour and voice over which was able to provide information about aircraft engines at the Nurtanio Laboratory using a QR Code. This application is expected to be able to help Public Relations and the New Student Admission Center at the Adisutjipto Aerospace Technology Institute. Application testing uses the Black Box method for system testing, and is carried out on several browsers with the results obtained that all browsers support the use of the TORERO application. User test results using the Likert scale method, obtained results with a success rate of 86.23% with a statement of strongly agree.